Juridical Analysis of the Crime of Narcotics Abuse Based on Law Number 35 of 2009 and the Criminal Code - Benny Eka Permana; Riza Zarzani (International Journal of Society and Law, 2024)
This study discusses the crime of narcotics abuse in a legal perspective regulated by Law Number 35 of 2009 concerning Narcotics and the Criminal Code (KUHP). Narcotics, while beneficial in the medical field, can have serious negative effects if abused, including physical and mental dependence. Narcotics abuse has become a complex social problem in Indonesia, affecting different levels of society. This study aims to analyze legal arrangements related to narcotics abuse based on the two laws. In addition, this study also highlights the role of rehabilitation as an alternative punishment for narcotics users in accordance with the principle of the double track system regulated in Law Number 35 of 2009.